No differences in O2-cost between V1 and V2 skating techniques during treadmill roller skiing at moderate to steep inclines - Losnegard, T.; Myklebust, H.; Hallén, J. (The Journal of Strength and Conditioning Research, 2012)
Elite crosscountry skiers use both the V1 and V2 techniques on moderate and steep inclines despite previous studies suggesting that the V1 technique is superior in terms of lower O2-cost and better performance on these inclines. However, this has not been studied in elite athletes, and therefore, the aim of this study was to compare O2-cost in these 2 main ski skating techniques in a group of 14 elite male crosscountry skiers (age: 24 ± 3 years, height: 184 ± 6 cm, weight: 79 ± 7 kg, V1 VO2max: 71.8 ± 3.5 ml/kg/min). With both techniques, the athletes performed submaximal trials for the determination of O2-cost on a roller ski treadmill at 4, 5, and 6° (3 m/s) and maximal trials at 8° (=3 m/s) for the determination of VO2max. Video-based kinematic analyses on cycle length and cycle rate (CR) were performed to unravel if there was any relation between these variables and O2-cost. No significant differences in O2-cost or VO2max between techniques were found. However, large and significant individual variations in physiological response were observed. V2 had a longer cycle length and lower CR than V1 did. No significant correlation was found between CR and O2-cost. This study shows that both V1 and V2 are appropriate techniques for optimizing O2-cost on moderate to steep inclines in elite skiers. However, individual variation suggests that ski skating performance on moderate to steep inclines may be determined by technique preferences of the athletes.